Human Gut Bacteriophageome: Insights Into Drug Resistance Mechanisms in Tuberculosis - Erfaneh Jafari; Reza Azizian; Mohsen Tabasi; Morteza Banakar; Kamran Bagheri Lankarani (Interdisciplinary Perspectives on Infectious Diseases)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a major global health burden. The emergence of drug-resistant strains presents a critical challenge in TB management. The recent research has explored the interaction between TB and the human gut bacteriophage community (phageome). The gut phageome plays a crucial role in regulating microbial diversity and functionality, and its composition and function have been linked to various health conditions. Examining the gut phageome through metagenomic analysis provides insights into its composition, role in health, and interactions with the host immune system. Exploring the interaction between the gut phageome and M. tuberculosis may reveal how phages affect the bacterium’s pathogenicity, survival, and mechanisms of drug resistance. Understanding the gut phageome’s impact on TB drug resistance could inform novel therapeutic strategies, such as phage therapy, and highlight the importance of microbiome-based interventions in combating drug-resistant TB strains. This review explores the role of the gut phageome in influencing drug resistance in TB, focusing on interaction mechanisms and potential therapeutic implications, synthesizing current research findings, and identifying knowledge gaps in this emerging field. This review also synthesizes the current evidence on the gut phageome’s role in TB drug resistance, focusing on phage-mediated horizontal gene transfer (e.g., rpoB, katG), immune modulation, and preclinical efficacy of mycobacteriophage therapies. Key findings highlight phage cocktails (e.g., DS6A, D29 LysB) as promising adjuncts to antibiotics, reducing M. tuberculosis burden in murine models. These insights advocate for phage therapy as a complementary strategy against drug-resistant TB, urging clinical validation to bridge the existing knowledge gaps.